Sentidos e significados do trabalho na Coordenadoria da Criança e do Adolescente/FUNCI da Secretaria de Direitos Humanos de Fortaleza-CE - Teixeira, Narah Cristina Maia (2012)
This thesis features the aim to analyze senses and meanings of the work performed at the Coordination of the Child and the Adolescent/Foundation of the Citizen Child and Family (FUNCI), a branch of the Human Rights Secretariat (SDH) of Fortaleza, state of Ceará, Brazil, based on a configuration of its objective and subjective dimensions. We specifically seek to: circumscribe the real working conditions at FUNCI; apprehend the ways in which employees think, feel and experience their own working activity; configure the standard of administration/control of these subjects; and discuss employees’ diverse positions regarding this reality. Therefore, we conducted a theoretical and fieldwork research that comprised of a literature review of the categories Capitalism, Work, State and Social Public Policy; interviews with employees of the Coordination of the Child and the Adolescent/FUNCI; investigation of documents and observation of the daily routine at the Foundation. This text comprises of an introduction, three chapters and final words. The introduction outlines the object based on a schedule of investigation, organized around main questions. Also in this section, I provide a detailed testimony of my professional experience at the Foundation of the Citizen Child and Family (FUNCI) as a way to circumscribe the object of study itself and configure its context and the diverse expressions of work precariousness in its objective and subjective dimensions. Thus I discuss the relevance of this study for the social and scientific fields. The first chapter approaches the analytical categories mobilized in the context of contemporaneity, e.g. capitalism; work precariousness; State and social policies; and precarious work in the field of social (public) policies. In this section, the topic ‘Work in the contemporary world: reconfigurations in times of precariousness’ underlies the fundamental theoretical discussions of this research. The section discusses the contemporary outline of the world of work, the unfolding precariousness of work in the history of capitalism and finally takes into account the new and precarious configurations of the work conducted behind social policies. The second chapter outlines the investigative process of this research. We approach questions derived from the theoretical and fieldwork research review, from configurations and outlines of the field and subjects and, at last, from the strategies of data collection and data analysis. The third and final chapter discusses the unveiling that was made possible through fieldwork research, in dialogue with the literature review. Thus follows the main considerations of this investigation.